2022
DOI: 10.3390/ijms23031631
|View full text |Cite
|
Sign up to set email alerts
|

K143R Amino Acid Substitution in 14-α-Demethylase (Erg11p) Changes Plasma Membrane and Cell Wall Structure of Candida albicans

Abstract: The opportunistic pathogen Candida albicans is responsible for life-threating infections in immunocompromised individuals. Azoles and polyenes are two of the most commonly used antifungals and target the ergosterol biosynthesis pathway or ergosterol itself. A limited number of clinically employed antifungals correspond to the development of resistance mechanisms. One resistance mechanism observed in clinical isolates of azole-resistant C. albicans is the introduction of point mutations in the ERG11 gene, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
(60 reference statements)
0
11
0
Order By: Relevance
“…The aim of this study was to investigate whether changes in the CW composition of C. albicans KS058 ( erg11∆ / ∆ ) and 10C1B1I1 ( ERG11 K143R / K143R ) mutants [ 28 ] correlate with altered cell surface hydrophobicity (CSH) and formation of biofilm. The results of CSH and biofilm assay are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this study was to investigate whether changes in the CW composition of C. albicans KS058 ( erg11∆ / ∆ ) and 10C1B1I1 ( ERG11 K143R / K143R ) mutants [ 28 ] correlate with altered cell surface hydrophobicity (CSH) and formation of biofilm. The results of CSH and biofilm assay are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that both point mutation ( K143R ) in the ERG11 gene (in C. albicans 10C1B1I1 strain) or deletion of this gene (in C. albicans KS058 strain) corresponds with changes in the plasma membrane (PM) and CW composition of C. albicans mutants [ 28 ]. CW remodeling can impact both virulence of C. albicans and the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the expression levels of HOG pathway members and CYP51s can affect the cellular ergosterol content. For example, in Cryptococcus neoformans , the Δ hog1 (MAPK) and Δ ssk1 (MAPKKK) mutants were found to generate significantly higher levels of cellular ergosterol than the WT [ 62 ], Δ Erg11B of A. fumigatus exhibited significantly reduced ergosterol content [ 63 ], and overexpression of Erg11 in Candida albicans elevated the ergosterol content [ 64 ]. Our studies showed that the HOG pathway and the transcription factors CsAtf1 and CsCyp51G1 are involved in fludioxonil sensitivity regulation in C. siamense , which prompted us to suggest a relevance between fludioxonil sensitivity and ergosterol biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…PMs were obtained as previously described [ 32 ]. Briefly, C. albicans CAF2-1 and KS028 cells were harvested (3 min, 6000 rpm) after 8, 14, or 24 h of culture (equal A 600 = 40 for all used strains) and lysis solution was added to the cells (1 M sorbitol, 0.1 M EDTA, 1% BME, 3 mg/mL zymolyase).…”
Section: Methodsmentioning
confidence: 99%